Sensing and adsorption study of gaseous phase chlorophenols on functionalized carbon nanotube membrane. (5th October 2018) - Kanchanatip, Ekkachai; Tulaphol, Sarttrawut; Den, Walter; Grisdanurak, Nurak; Miao, Hsin‐Yuan; Yan, Mi
Abstract : The adsorption equilibrium isotherms as well as gas sensing of three chlorinated phenolic compounds (CPCs) including phenol, 2‐chlorophenol, and 2, 4‐dichlorophenol by acid‐functionalized carbon nanotube (CNT) membrane were studied. CNTs were synthesized via floating catalyst chemical vapor deposition method at 800°C and then functionalized with a mixture of HNO3 and H2 SO4 . The functionalized CNTs were vacuum filtered to form CNT membranes. The adsorption isotherm followed the Langmuir adsorption model better than the Freundlich model, suggesting monolayer adsorption. The maximum adsorption capacities were found to be 61.35, 93.46, and 104.17 mg g −1 for phenol, 2‐chlorophenol, and 2, 4‐dichlorophenol, respectively. The desorption energy determined via thermogravimetric analysis indicates that adsorption of all three CPCs onto the CNT membranes belonged to chemisorption type. For the gas sensing test, the CNT membrane showed fast response to the tested CPCs with good stability and repeatability. The sensitivity values obtained were 5.39 × 10 −2, 3.35 × 10 −2 and 2.58 × 10 −2 for 2, 4‐dichlorophenol, 2‐chlorophenol, and phenol, respectively. It is noteworthy that the adsorption capacity and sensitivity of the CNT membrane to the target gases increased with the increase in the number of chlorine atoms in the phenolic compounds. © 2018 American Institute of Chemical Engineers Environ Prog, 38: S315–S322, 2019